Next generation sequencing identified novel truncating mutations in BBS9 causing Bardet Biedl syndrome in two Iranian consanguineous families: two novel pathogenic variants in BBS9 gene - Akbaroghli, Susan; Kooshavar, Daniz; Golchehre, Zahra; Karamzade, Arezou; Saberi, Mohammad; Alaei, Mohammad Reza; Abbasi Sadegh, Masoud; Asadollahi, Mostafa; Keramatipour, Mohammad (Iranian Journal of Child Neurology, 2022)
Abstract Objectives Bardet-Biedl syndrome (BBS) is an autosomal recessive pleiotropic ciliopathy, which includes multi-organ clinical manifestations. The known genes involved in the development of the disease account for the causality in about 80% of the examined cases. Materials & Methods We investigated two Iranian unrelated clinically diagnosed BBS patients, using a targeted next-generation sequencing panel consisting of 18 known BBS genes. The detected variants were investigated in the pedigree and studied using in silico tools for their pathogenicity. Patients’ phenotypes were also assessed. Results Novel homozygous variants were detected in BBS9 gene in each patient, c.2014C>T, p.Gln672Ter and c.673_674insAA, p.Gln225GlnfsX10. The variants were segregated in the corresponding pedigree and were authenticated to obtain enough evidence to be categorized as pathogenic variants. Conclusion Patients with truncating mutations in the same gene seem to show similar phenotypic features. Detection of novel and family-specific mutations is typically expected in the genetic hereditary diseases in Iran, which can finally lead to prevent the recurrence of the disease in the consanguineous marriages.